Analisis RAPD ( Random Amplified Polymorphic DNA)untuk Diferensiasi Mycobacteriun tuberculosis isolat klinik sensitif INH dan Rifampisin di Makassar - Yusuf, Zuhriana K. (Sainstek, 2010)
This study aims to find out: (1) whether there is a genetic diversity on M.tuberculosis isolat clinic that is sensitif to INH dan rifampisin with RAPD method, and (2) the description of its polimorfism diferentiation. The research samples include 5 Mycobacteriun tuberculosis isolate that is sensitive to INH and rifampisin. The study includes DNA extraction using Wizard Genom DNA purification method, amplification using 5 primer: A-2 (5 TGCCGAGTCG 3 , 70% G+C ), OPN-09 ( 5TGCCGGCTTG 3, 70% G+C), N-9 (5 TGCCGGCTTG 3, 70% G+C), BG-66 (5CGACGCTGCG 3, 80% G+C) , 80% G+C), U-19 ( 5 GTCAGTGCGG 3, 70% G+C), and electroforesis. The isolat genetic diversity was analysed by using Dendro Unweighted Pair Group Method of Aritmethic (UPGMA) : A Dendogram Construction Utility method from Dr. Santi GarciaValive/2009. The results show that there is a genetic diversity on the 5 isolate Mycobacterium tuberculosis that are sensitive to INH and rifampisin, amplified with 5 primer. The size of amplified DNA bands is between 200-1100bp. The genetic variation can be seen in the number of fragments, the size of fragments and the number of polimorfik bands. The polimorfik percentage of the isolate is between 66.67% - 100%, or 80.28 in average. The UPGMA analysis results in a dendogram with a group cooficient of 0 40% or a diversity of 60 100%. Keywords: RAPD, Mycobacterium tuberculosis, sensitive to INH and rifampisin.